Aplikasi Digital Berbasis Artificial Intelligence untuk Latihan Bicara Siswa Cerebral Palsy - Annisa Annisa; Nur Anifah Lubis; Nurul Annisa; Novia Biliara (Jurnal Pendidikan Kebutuhan Khusus, 2026)
Cerebral Palsy (CP) is a non-progressive motor disorder frequently accompanied by cognitive, visual, and speech impairments, which often result in communication barriers and difficulties in verbal learning. This study aims to design an artificial intelligence (AI)-based speech training application to support children with CP in improving their verbal communication skills. The research employed a Research and Development (R&D) approach, consisting of needs analysis, interface design, and integration of visual, audio, text, camera, and AI components to provide automated pronunciation feedback. The outcome of this study is a prototype design of an application featuring a simple interface, large buttons, and child-friendly navigation. The AI system is designed to deliver immediate feedback on pronunciation errors, thereby enhancing interactivity, motivation, and learner independence. The findings are expected to contribute to the development of inclusive digital learning media and the application of AI in speech therapy, ultimately expanding communication access and learning opportunities for children with special needs, particularly those with Cerebral Palsy.